Predictors of Depressive Symptoms in Rural Farm Women Aged 50 and Over - Cheryl Dean Witt; Deborah B. Reed; Mary Kay Rayens (Rural Nurse Organization; Binghamton University, 2020)
Purpose: Aspects of farming and farm life can contribute to higher levels of depressive symptoms resulting in an increased risk for injury and development of chronic disease and a decrease in overall quality of life. Rural farm women can be subjected to stressors from farming as an occupation, their role within the agrarian culture, and life in a rural area. The purpose of this study was to examine the associations of demographic characteristics, agricultural occupational factors, and health indicators with depressive symptoms among farm women aged 50 years and older. Methods: Secondary analysis of cross-sectional data from the Sustained Work Indicators of Older Farmers Study (2002-2006) was used to examine the influence of factors on depressive symptoms of older (> 50 years) female farmers (N= 358) from North Carolina and Kentucky. The study was framed by a modified version of the Biopsychosocial Model. Logistic regression was conducted to examine the relationships between demographics, perceived health status, active coping score, perceived stress, and factors specific to farm work and depressive symptoms. Findings: Participants' depressive symptoms status (high vs. low) was predicted by their race/ethnicity, years of education, adequacy of income for vacation, perceived health status, perceived stress, and active coping. Conclusion: This study increases our understanding of the factors associated with depressive symptoms in farm women, but also identifies significant gaps in our knowledge of depressive symptoms among this population. The multifaceted dimensions of depressive symptoms revealed indicate a crucial need to more fully explore the interrelationship among the dimensions of the conceptual model and the physical and mental health of farm women. Additional knowledge gained from these studies will assist in the development of assessment instruments, skills, and plan of care specific to the needs of farm women; thus optimizing the health care of farm women. Key words: rural women, farm women, depressive symptoms, farm life